2018
DOI: 10.1002/celc.201801526
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Sulfur Doped Carbon Cloth as Current Collector and Polysulfide Immobilizer for Magnesium‐Sulfur Batteries

Abstract: The combination of Mg and S is considered as an attractive candidate for metal-sulfur batteries due to their high volumetric energy density and adequate existence of natural resources. However, MgÀ S batteries suffer from polysulfide dissolution and shuttling which leads to reduced cycle life and stability.Here we report the significance of the chemical interaction between magnesium polysulfide and N, S dual-doped carbon cloth for improving the cycle life. Compared to undoped carbon cloth, the dual-doped carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Apart from the commercial current collectors, Muthuraj et al developed an effective current collector, which is stable against corrosive electrolytes and can also catch polysulfides. Very recently, they presented a N‐, S‐dually doped carbon cloth (DCC) as current collector, which possesses a 3D interconnected porous structure that provides superior cycle stability and high conductivity .…”
Section: Cathode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the commercial current collectors, Muthuraj et al developed an effective current collector, which is stable against corrosive electrolytes and can also catch polysulfides. Very recently, they presented a N‐, S‐dually doped carbon cloth (DCC) as current collector, which possesses a 3D interconnected porous structure that provides superior cycle stability and high conductivity .…”
Section: Cathode Materialsmentioning
confidence: 99%
“…The results showed that after the addition of IL to the electrolyte the initial capacity and the capacity at the 20th cycle increased to 800 mAh g −1 sulfur and 280 mAh g −1 sulfur , respectively . Due to the attractive electrochemical properties and the simplicity in synthesis, this type of electrolytes was also utilized by Vinayan et al, Yu and Arumugam, Friedrich and co‐workers, and Muthuraj et al, though with combinations of different cathodes, anodes and current collectors.…”
Section: Electrolyte Systemsmentioning
confidence: 99%
“…Recently, nitrogen and sulfur dual doped carbon cloths have been used as current collectors and polysulfide reservoir in Mg−S batteries . It was observed that elemental doping not only improves the ion diffusion in carbon cloths but also reduces the voltage hysteresis loss during charge/discharge.…”
Section: Flexible Carbon Cloth‐based Hybrids For Electrochemical Supementioning
confidence: 99%
“…[106] Recently, nitrogen and sulfur dual doped carbon cloths have been used as current collectors and polysulfide reservoir in MgÀ S batteries. [25] It was observed that elemental doping not only improves the ion diffusion in carbon cloths but also reduces the voltage hysteresis loss during charge/discharge. Thus doping can be thought to be more advantageous for improving energy storage in carbon cloths and it was evident from recently reported nitrogen-doped carbon cloths where doping was carried out via simple and facile nitrogen plasma approach.…”
Section: Growth Of Carbon Nanomaterials or Their Analogues On Carbon mentioning
confidence: 99%
“…The energy storage mechanism for all metal-sulfur batteries follows a conversion type mechanism [13,[150][151][152][153][154]. A simple version of this reaction occurs for lithium, sodium and magnesium [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166]. In this mechanism the sulfur in the cathode is reduced and forms a metal sulfide complex with the metal ions from the electrolyte solution, as in Equation 22.…”
Section: Metal-sulfur Batteriesmentioning
confidence: 99%